Publishing with Open Journal Systems (OJS): the engaged university and library support at the University of Stavanger - Farmanbar, Mina; Kolstrup, Per (Septentrio Conference Series, 2020)
Increasing the role of libraries in academic journal publishing activities and journal hosting has become an important subject in the library world in the past few years. The purpose of this study is to present the role of the libraries at University of Stavanger (UiS) in the context of library-as-publisher. Within this category, open access (OA) journal publishing has been a popular service offered by libraries, rapidly attracting researchers' attention. The University Libraries at University of Stavanger (UiS) have a long history of promoting and supporting open access initiatives. The Libraries have established and continue to build, host and maintain an operative open access institutional repository (UiS Brage) for scientific works in full text. From 2018, UiS libraries started using a journal management system to facilitate the open access scholarly publishing and therefore support transferring and updating of established the existing journals and the lunching of new ones. The Open Journal Systems (OJS) from Public Knowledge Project (PKP) is used which is the most common journal management system being discussed frequently in literature. Currently, the UiS Libraries repository host four active open access journals, with some others under development. All these journals reside within the same OJS implementation with the same design and layout on top, however, at the individual journal level there are also options for some customization. UiS libraries initially support all the steps of the journal creation and development process but train the editors and the subsequent users to engage in some part of the process. The library IT-Engineer and Information Technology Department (IT) manage OJS server, maintain the OJS database and software, and performs the layout and design customization and development and initial technical configuration for the new journals. From the viewpoint of IT, there is a need for several technical skills such as web design skills to customize the style sheets and web layout, graphic design skills to produce banners, logos and cover pages whereas the editorial workflow process may require skills on copy-editing and proofreading of articles. OJS is a template-based platform but when it comes to front-end design, it has its limitation. There are certain limitations which make it difficult to get to the details of the article. For instance, when an article comes with a long abstract or number of references, the web-page becomes unfriendly. Another challenge is when PKP launches a new OJS update. Some features cannot be migrated, and you may lose them. Furthermore, users may find it hard to adapt to the new version. The biggest challenge to the OJS is the learning curve. There are some faculty members who have had some frustrations with the software. While it is a free and open source platform, the time, technical skills and programming abilities are still associated with the costs. In this poster we provide you with the challenges and lessons learned so far by the libraries at Stavanger University.